Dinamika Resistensi dan Adopsi QRIS pada UMKM Makassar: Analisis Kualitatif dengan Pendekatan Teori Nudge - Zaimar, Fina Ruzika; Adriansyah, Adriansyah; Haruna, Hasisa; Windarsari, Wiwin Riski; Ridha, Achmad (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2025)
This study aims to explore the dynamics of resistance and adoption of the Quick Response Code Indonesian Standard (QRIS) among Micro, Small, and Medium Enterprises (MSMEs) in Makassar City using a qualitative approach and the Nudge Theory framework. This study focuses on an in-depth understanding of the factors that encourage and hinder QRIS adoption, by exploring the perspectives of both user and non-user businesses. Data were obtained through in-depth interviews with 10 MSMEs in the culinary sector and analyzed using thematic analysis methods. The results show that the decision to adopt QRIS is influenced by factors such as ease of access (simplification), social influence (social norm), default option settings(default option), information visibility (salience), the way of conveying information (framing), and providing feedback (feedback). Conversely, resistance to QRIS is driven by limited digital literacy, a lack of understanding of the benefits, and concerns about the risks of digital transactions. This finding confirms the relevance of Nudge Theory in explaining MSME decision-making behavior. This research contributes to the development of behavior-based strategies to promote digital financial inclusion in the MSME sector. Keywords: QRIS, MSMEs, Nudge Theory, Technology Resistance, Digital Financial Inclusion